New York's Subterranean Paradoxes: A Review Of Subway - Samuel Merrill (Opticon1826, 2014)
This review considers the recent re-publication of Bruce Davidson’s Subway series of photographs, and their exhibition at C/O in Berlin, Germany. As such, this review positions Davidson’s photographs both in relation to wider cultural analyses that highlight the paradoxical nature of subterranean space, and within a selective genealogy of subway representations. Furthermore, it views the reinvigorated interest in Davidson’s work to be reflective of the growing popularity of subterranean space that has recently re-emphasised its cultural potential.